Fiscal Policy, the Real Exchange Rate and Commodity Prices - Reinhart, Carmen (IMF Working Papers; Working Paper ;, 1990)
The role of the international commodity market in transmitting disturbances is considered in a model that incorporates commodities as an input in production. The analysis employs a three-country framework: a liquidity-constrained commodity supplier and two industrial countries that import the commodity, export differentiated manufactured goods and hold the outstanding debt of the commodity exporter. In this setting the impact of changes in fiscal policy, commodity supplies, and the real interest rate are assessed. Particular attention is paid to the responses of the real exchange rate, commodity prices, and the international distribution of debt to the various shocks.